From a Cause to a Style : Modernist Architecture's Encounter with the American City - Glazer, Nathan (Book collections on Project MUSE., 2007)
Modernism in architecture and urban design has failed the American city. This is the decisive conclusion that renowned public intellectual Nathan Glazer has drawn from two decades of writing and thinking about what this architectural movement will bequeath to future generations. In From a Cause to a Style, he proclaims his disappointment with modernism and its impact on the American city. Writing in the tradition of legendary American architectural critics Lewis Mumford and Jane Jacobs, Glazer contends that modernism, this new urban form that signaled not just a radical revolution in style but.